2010
DOI: 10.1073/pnas.1011116107
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin secretion stimulated by β 1 -adrenergic receptors in cultured ghrelinoma cells and in fasted mice

Abstract: Ghrelin, an octanoylated peptide hormone produced in the stomach, rises dramatically in mouse plasma during chronic severe calorie deprivation, an event that is essential to maintain life. The mechanism for this increase is not understood. Here, we study the control of ghrelin secretion in tissue culture cells derived from mice bearing ghrelinomas induced by a tissue-specific SV40 T-antigen transgene. We found that the ghrelin-secreting cells express high levels of mRNA encoding β 1 -adrenergic receptors. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
221
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(240 citation statements)
references
References 30 publications
15
221
2
2
Order By: Relevance
“…Of the 10 peptide hormones tested, none stimulated ghrelin secretion in either PG-1 or SG-1 cells. In contrast, norepinephrine stimulated ghrelin secretion two-to threefold at a half-maximal concentration of 0.1 mM in both cell lines (Zhao et al 2010b). Forskolin mimicked the norepinephrine effect, indicating that the neurotransmitter acted by activating adenylyl cyclase (Fig.…”
Section: How Do Gastric Ghrelin-secreting Cells Respond To Hypoglycemia?mentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 10 peptide hormones tested, none stimulated ghrelin secretion in either PG-1 or SG-1 cells. In contrast, norepinephrine stimulated ghrelin secretion two-to threefold at a half-maximal concentration of 0.1 mM in both cell lines (Zhao et al 2010b). Forskolin mimicked the norepinephrine effect, indicating that the neurotransmitter acted by activating adenylyl cyclase (Fig.…”
Section: How Do Gastric Ghrelin-secreting Cells Respond To Hypoglycemia?mentioning
confidence: 99%
“…Earlier indirect evidence suggested that the sympathetic nervous system might stimulate ghrelin secretion (Mundinger et al 2006;Hosoda and Kangawa 2008), but the hypothesis could not be tested directly, owing to the paucity of ghrelin-secreting cells in the stomach. To circumvent this problem, we and our colleagues created lines of ghrelin-secreting tumor cells that could be maintained in tissue culture (Zhao et al 2010b). For this purpose, we created a BAC transgene encoding oncogenic SV40 T-antigen driven by the promoter of the ghrelin gene.…”
Section: How Do Gastric Ghrelin-secreting Cells Respond To Hypoglycemia?mentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial stress leads to elevations in circulating levels of acyl-ghrelin. As sympathoadrenal tone is increased in stress, speculatively, this stress-induced elevation may involve stimulation of ␤ 1 -adrenergic receptors on ghrelin cells, a pathway that has been implicated in ghrelin release in response to fasting [44,51]. Ghrelin, in turn, interacts with its receptor, GHSR, which is distributed throughout the brain and periphery [52].…”
Section: Ghrelin Levels Increase After Pictures Showing Foodmentioning
confidence: 99%